2015
DOI: 10.1371/journal.pone.0128865
|View full text |Cite
|
Sign up to set email alerts
|

DNA Marker Transmission and Linkage Analysis in Populations Derived from a Sugarcane (Saccharum spp.) x Erianthus arundinaceus Hybrid

Abstract: Introgression of Erianthus arundinaceus has been the focus of several sugarcane breeding programs in the world, because the species has desirable traits such as high biomass production, vigour, ratooning ability and good resistance to environmental stresses and disease. In this study four genetic maps were constructed for two intergeneric populations. The first population (BC1) was generated from a cross between an Erianthus/Saccharum hybrid YC96-40 and a commercial sugarcane variety CP84-1198. The second popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Our result agrees with other studies that used AFLP [78,79], cpSSR [80], TRAP [21,30,59], SRAP [55] and SSR [3,81] markers. The introgression of alleles of the Erianthus genus in sugarcane breeding programs, mainly from E. arundinaceus, has been evaluated in recent years to increase adaptability, disease resistance, drought resistance and biomass production [82,83]. Despite this, further studies may be conducted to evaluate other regions of the genome closely related to the outstanding traits of the Erianthus genus.…”
Section: Discussionmentioning
confidence: 99%
“…Our result agrees with other studies that used AFLP [78,79], cpSSR [80], TRAP [21,30,59], SRAP [55] and SSR [3,81] markers. The introgression of alleles of the Erianthus genus in sugarcane breeding programs, mainly from E. arundinaceus, has been evaluated in recent years to increase adaptability, disease resistance, drought resistance and biomass production [82,83]. Despite this, further studies may be conducted to evaluate other regions of the genome closely related to the outstanding traits of the Erianthus genus.…”
Section: Discussionmentioning
confidence: 99%
“…(2 n = 20, 30, 40, 60) [ 7 ]. On the basis of the analysis of repulsion-phase linkage, Chen et al [ 8 ] reported that Erianthus behaves like a true autopolyploid. Of the seven species, E. arundinaceus and E. procerus have recently attracted attention for their use in Erianthus and sugarcane breeding to increase biomass production [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…and E . arundinaceus are polyploid plants with large genomes and many homologous sequences 24,25 . However, researchers can use the genome sequencing strategy for wheat, which is called “break up the whole into parts,” or “BAC BY BAC,” for Saccharum spp.…”
Section: Introductionmentioning
confidence: 99%